2010
DOI: 10.1515/epoly.2010.10.1.224
|View full text |Cite
|
Sign up to set email alerts
|

MgH2/PEG initiating system for ring opening polymerization of lactone and lactide

Abstract: Dihydroxy-terminated poly(ethylene glycol) and MgH 2 form an efficient initiating system for the ring opening polymerization of ε-caprolactone and Llactide. Polycaprolactone-block-polyethylene glycol-block-polycaprolactone and polylactide-block-polyethylene glycol-block-polylactide were synthesized in bulk at 120 °C for 16 h under argon. MgH 2 provided a faster polymerization rate compared with other initiating systems based on non toxic metals used under vacuum. Molecular weight of copolymers varied according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…At the lyophilization settings employed in this study, both glucose and PEG are found to be unsuitable as cryoprotectants for the freeze-drying of PBCA-MB. This is expected to be due to the low collapse temperature and the low glass transition temperature of glucose and PEG (i.e., −41 °C and −62.3 °C, respectively), resulting in disintegration and/or coalescence of PBCA-MB during freeze-drying [28,29]. For efficient lyophilization, freeze-drying should be carried out at temperatures below the collapse temperature of the product [28].…”
Section: Resultsmentioning
confidence: 99%
“…At the lyophilization settings employed in this study, both glucose and PEG are found to be unsuitable as cryoprotectants for the freeze-drying of PBCA-MB. This is expected to be due to the low collapse temperature and the low glass transition temperature of glucose and PEG (i.e., −41 °C and −62.3 °C, respectively), resulting in disintegration and/or coalescence of PBCA-MB during freeze-drying [28,29]. For efficient lyophilization, freeze-drying should be carried out at temperatures below the collapse temperature of the product [28].…”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of PCL, racemization is not an issue, which gives greater scope for exploiting calcium hydride to its full potential as an initiator. Analogous studies using magnesium hydride showed efficient polymerization of both PLA and PCL copolymers of PEG and poly(vinyl alcohol) at 120 °C. However, the polymerization conditions were limited in scope which restricted the analysis of the polymerization mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For the synthesis of PCL, racemization is not an issue, which gives greater scope for exploiting calcium hydride to its full potential as an initiator. Analogous studies 13,14 using magnesium hydride showed efficient polymerization of both PLA and PCL copolymers of PEG and poly(vinyl alcohol) at 120 ∘ C. However, the polymerization conditions were limited in scope which restricted the analysis of the polymerization mechanism. In the study reported herein, the effect of varying synthetic parameters such as temperature and reactant concentration has been investigated in detail in order to better understand the mechanism of polymerization.…”
Section: Introductionmentioning
confidence: 99%